Predictive Analysis Of Demand Of Electric Vehicles In Malaysia And Its Potential - Nabli, Muaz (Universiti Sains Malaysia, 2022)
For the purpose of this investigation, information regarding issues and causes of growth rate of Electric Vehicle (EV) will be sourced from research journals and articles that have been previously published. These sources will focus on the advantages and disadvantages of electric vehicles (EVs) in general, with particular attention paid to the advantages for EV users, such as the availability of public charging stations, the volume of EV sales, and the production of oil (i.e., diesel, petrol). A variety of factors are contributing to the precipitous rise in the demand for electric vehicles (EVs) in industrialised nations. As more people purchase completely electric or plug-in hybrid vehicles, there has been an accompanying rise in the demand for energy. However, the number of electric cars on the road in Malaysia is not nearly as high as it should be. The purpose of this study is to investigate the aspects that will shed light on the reasons why this is the case as well as the potential ways in which it might be changed. To determine what the most probable outcome will be, many potential outcomes will be investigated. In this article, prediction analysis will be made based on many scenarios that have led to this position, and we will also detail possible solutions to the problems that have arisen. It shows that EV will increase if less production rate for oil(per gallon) as this will cause in risen in petrol price rate and more charging infrastructure for EV is built in Rehat & Rawat (R&R), shopping complex, and rural area.